PRODUKTIVITAS TENAGA KERJA PADA USAHATANI JAGUNG MANIS (Zea mays saccharata L) DI DESA MANTUYAN KECAMATAN HALONG KABUPATEN BALANGAN PROVINSI KALIMANTAN SELATAN - Yayuk Minta Wahyuningsih; Zuraida Zuraida (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
The reaserch was conducted in Mantuyan village,Halong district,for sampling the farmers were taken by sensus namely that  as much as 20 farmers.Outpouring of labor in the family bigger role that 12,64 % out family that much 87,36 %.The index value in labour productivity of Rp 48.058,30 higher than the wage rate of Rp 45.000,.while for the value of land productivity of 8,2 ton/ha.